Supplementation of Nodulisporium sp. KT29 induced by Vibrio harveyi as an immunostimulant for controlling vibriosis in vannamei white shrimp under marine culture system - Dinamella Wahjuningrum; Teuku Reza Efianda; Kustiariyah Tarman; Munti Yuhana; Irzal Effendi; Fazril Saputra (Jurnal Akuakultur Indonesia)
ABSTRACT